-8=-7(-4x+8)+8(x-3)

Simple and best practice solution for -8=-7(-4x+8)+8(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8=-7(-4x+8)+8(x-3) equation:



-8=-7(-4x+8)+8(x-3)
We move all terms to the left:
-8-(-7(-4x+8)+8(x-3))=0
We calculate terms in parentheses: -(-7(-4x+8)+8(x-3)), so:
-7(-4x+8)+8(x-3)
We multiply parentheses
28x+8x-56-24
We add all the numbers together, and all the variables
36x-80
Back to the equation:
-(36x-80)
We get rid of parentheses
-36x+80-8=0
We add all the numbers together, and all the variables
-36x+72=0
We move all terms containing x to the left, all other terms to the right
-36x=-72
x=-72/-36
x=+2

See similar equations:

| 17=x÷3 | | Y+168+5x-48=180 | | 1/x-x-1/8=6 | | 2(×+4)-5=2x+3 | | 4(m-4)+7m=-93 | | 1/3(9x+27)-4=1/2(2×+54) | | x=1/4=2x=3/12=7/9 | | -3y-11=9y+13 | | 12x+7=3x+4 | | (7x^2-488)=0 | | -3y-11=9y+14 | | -30-a=-2(8+2a)-4a | | |x+2|=5-x | | 8(r+2=64 | | 9+3x+(2x-2)=67 | | (x-12)+x=-5 | | 6-6x=6(x+7) | | 5x-8=123 | | 20-6x=50-26x | | -6(x-3)-4(x-2)=-4 | | 1/4(a+10)=10 | | n=13÷-1 | | 13+2x-14=x | | (3x-11)+x=49 | | 3x+4=7(x+2)+2 | | 10+x=5(x+2) | | 6+1x=33-2x | | m-12/4-4m-3/5=2 | | 9+3x+2x-2=67 | | 3x-7=9x-25 | | (x-4)(x-18)=x-14 | | 40-5x=-55 |

Equations solver categories